Angiogenesis in cutaneous malignant melanoma and potential therapeutic strategies. Issue 11 (November 2009) - Basu, Bristi; Biswas, Swethajit; Wrigley, Jessica; Sirohi, Bhawna; Corrie, Pippa
Metastatic melanoma (MM) carries a dismal prognosis, as it is largely resistant to conventional cytotoxic chemotherapy, biochemotherapy and immunotherapy. There is, therefore, a pressing need to identify new, effective treatments to improve outcomes from MM. Innovative approaches in oncology drug development include anti-angiogenic strategies, in the form of monoclonal antibodies and small-molecule kinase inhibitors. In this review we aim to present current concepts and controversies surrounding the role of angiogenesis and anti-angiogenic therapies in MM, alluding to other tumor types in which increasing knowledge may supply avenues for future directions in melanoma research and management. An overview of angiogenesis and its importance in melanoma progression is presented, highlighting the key molecules that represent potential therapeutic targets. The results of using anti-angiogenic strategies in preclinical and clinical trials are discussed and future perspectives for anti-angiogenic therapies in MM are considered.